2018
DOI: 10.3389/fimmu.2018.01537
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lactic Acid Bacteria Against TLR4 Induced Inflammatory Response in Hepatoma HepG2 Cells Through Modulation of Toll-Like Receptor Negative Regulators of Mitogen-Activated Protein Kinase and NF-κB Signaling

Abstract: The beneficial effects of probiotics in several liver diseases have been investigated in both animal and clinical models; however, the precise mechanisms responsible for their effects have not yet been elucidated. Gut transmitted endotoxins such as LPS have been shown to play critical roles in hepatic inflammation and injury. Therefore, in this study, we investigated the beneficial role of selected lactic acid bacteria (LABs) on reduction of hepatic steatosis (HS) and attenuation of LPS induced inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 50 publications
(62 reference statements)
2
40
0
Order By: Relevance
“…We found that 5%LHFM_Cit-4mM was able to induce all negative regulators mRNA expression in non-LPS treated cells, although IRAK-M and Tollip were not statistically significant (P = 0.55 and P = 0.17, respectively). When incubated with LPS, it resulted in activation of A20 and IRAK-M expression in this study that is consistent with previous findings 16 . However, other studies by Li, et al 57 and Finamore, et al 58 demonstrated that A20, Tollip and IRAK-M expressions were suppressed in ETEC infection.…”
Section: Discussionsupporting
confidence: 93%
“…We found that 5%LHFM_Cit-4mM was able to induce all negative regulators mRNA expression in non-LPS treated cells, although IRAK-M and Tollip were not statistically significant (P = 0.55 and P = 0.17, respectively). When incubated with LPS, it resulted in activation of A20 and IRAK-M expression in this study that is consistent with previous findings 16 . However, other studies by Li, et al 57 and Finamore, et al 58 demonstrated that A20, Tollip and IRAK-M expressions were suppressed in ETEC infection.…”
Section: Discussionsupporting
confidence: 93%
“…The purity of the RNA was checked, after which it was used to synthesize cDNA using a BioRad thermal cycler (BIORAD, Hercules, CA, USA). Next, RT-PCR was performed using a 7300 real-time PCR system (Roche Applied Science, Indianapolis, IN, USA) with SYBR green and primers [27]. The reaction mixture had a total volume of 20 μl that contained 1 μl of cDNA and 19 μl of master mix including SYBR green and both forward and reverse primers (1 pmol/ μl).…”
Section: Real-time Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…L. plantarum revealed some anti-inflammatory activity through inhibition of CXCL8 expression and increase of the anti-inflammatory cytokine IL-10 in Caco-2 cells [ 54 , 55 ] while a combination of selected LAB ( L. plantarum DU1, L. farciminis , Weissella cibaria DU1, and L. pentosus ) reduces hepatic steatosis and attenuates the inflammatory response in vitro through IL-6, CXCL8, CCL2, and TNF-α inhibition via modulation of Toll-like Receptor (TLR) negative regulators of the MAPK and NF-κB pathways [ 56 ]. Ex vivo studies in ileal and colonic mucosa from 10 post-infectious irritable bowel syndrome patients (PI-IBS), and 10 healthy controls pretreated with L. casei DG (LC-DG) showed that LC-DG significantly reduced pro-inflammatory cytokines IL-1α, IL-6 and IL-8 mRNA levels as well as TLR-4 protein expression after lipopolysaccharide (LPS) stimulation [ 57 ].…”
Section: Resultsmentioning
confidence: 99%